Lithium manganese iron phosphate positive electrode material and preparation method thereof

By forming a phosphorus-rich shell layer during the preparation of lithium manganese iron phosphate positive electrode material, the problem of manganese dissolution and high resistivity during the circulation process is solved, and its cycle life and electrical properties are significantly improved.

CN119873776APending Publication Date: 2025-04-25NANTONG RESHINE NEW MATERIAL CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202311375375.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-23
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The manganese dissolution of lithium manganese iron phosphate positive electrode material during circulation causes problems such as fast voltage platform decline, poor cycle life, and high powder resistivity, which hinders its large-scale commercial application.

Method used

During the preparation of lithium manganese iron phosphate positive electrode material, phosphorus-containing additives are added and distributed on the surface of the particles during the secondary sintering process to form a phosphorus-rich shell layer, thereby preventing manganese from dissolution and reducing powder resistivity.

Benefits of technology

It effectively slows down the decay rate of the voltage platform during the cycle and improves the cycle life of lithium manganese iron phosphate positive electrode material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119873776A_ABST
    Figure CN119873776A_ABST
Patent Text Reader

Abstract

The invention discloses a lithium manganese iron phosphate positive electrode material and a preparation method thereof, and relates to the technical field of lithium ion batteries. The preparation method comprises the steps that raw materials and a solvent are evenly mixed, a primary mixture is obtained, and the raw materials comprise a phosphorus-containing compound, a manganese-containing compound, an iron-containing compound, a lithium-containing compound and a carbon-containing compound; performing primary pretreatment and primary sintering on the primary mixture to obtain a primary sintered material; uniformly mixing the primary sintered material, an additive and a solvent to obtain a secondary mixed material, and the additive contains phosphorus element; the secondary mixed material is subjected to secondary pretreatment and secondary sintering, and a secondary sintered material is obtained; secondary sintering is carried out, so that phosphorus in the additive is distributed on the particle surface of the secondary sintering material, and a phosphorus-rich shell layer is formed; and carrying out post-treatment on the secondary sintered material to obtain the lithium manganese iron phosphate positive electrode material. The powder resistivity of the positive electrode material can be reduced, so that the decline rate of a voltage platform in the circulation process is slowed down, and the cycle life of the lithium manganese iron phosphate positive electrode material is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a lithium iron manganese phosphate positive electrode material and a preparation method thereof. Background Art

[0002] At present, the commercial lithium-ion battery positive electrode materials mainly include ternary (nickel cobalt manganese oxide), lithium manganese oxide, and lithium iron phosphate materials. Among them, ternary materials have the highest energy density, but because they contain rare metal nickel and cobalt elements, the materials are expensive and their safety is poor. When they are commercially applied, components to prevent thermal runaway need to be added at the system level, which further increases their costs. Compared with ternary materials, lithium manganese oxide materials have lower costs, but due to the dissolution of manganese during their use, the Chiang-Taylor effect leads to poor cycle life, and the safety of lithium manganese oxide materials is also poor. Lithium iron phosphate materials have significant safety and cost advantages among the above three materials. After years of development, the lithium iron phosphate industry has become increasingly mature in material design and manufacturing technology. Its actual application capacity is close to the theoretical capacity, and the powder compaction density is as high as 2.6g / cc. Its performance potential has been basically fully developed.

[0003] With the continuous development of the new energy industry and the continuous advancement of material technology, the industry's innovation and progress are still continuing in an environment where the above three material systems have become increasingly mature. Among them, a variety of new positive electrode materials have been proposed, developed and applied, including high-voltage spinel nickel-manganese binary materials, lithium-rich manganese-based materials, and lithium iron manganese phosphate materials. Among them, lithium iron manganese phosphate materials have similar safety and capacity to lithium iron phosphate, and their voltage platform is about 0.6V higher than that of lithium iron phosphate. The mass energy density is 10~20% higher than that of lithium iron phosphate materials. It has a significant energy density advantage. Therefore, lithium iron manganese phosphate materials are regarded as an upgraded version of lithium iron phosphate materials, with significant cost advantages per watt-hour.

[0004] However, there are still many problems in the performance of lithium manganese iron phosphate materials. For example, manganese dissolution during the cycle causes rapid voltage platform decay, poor cycle life, and high powder resistivity, which hinders the large-scale commercial application of lithium manganese iron phosphate materials. Summary of the invention

[0005] The object of the present invention is to provide a lithium manganese iron phosphate positive electrode material and a preparation method thereof, which can reduce the dissolution rate of manganese during battery cycling.

[0006] To achieve the above object, a technical solution adopted by the present invention is: to provide a method for preparing a lithium manganese iron phosphate positive electrode material, comprising: The raw materials are mixed evenly with a solvent to obtain a primary mixture, wherein the raw materials include a phosphorus-containing compound, a manganese-containing compound, an iron-containing compound, a lithium-containing compound and a carbon-containing compound; The primary mixed material is subjected to a pre-treatment and a sintering to obtain a primary sintered material; The primary sintering material, additive and solvent are uniformly mixed to obtain a secondary mixed material, wherein the additive contains phosphorus element; The secondary mixed material is subjected to secondary pretreatment and secondary sintering to obtain a secondary sintered material; the secondary sintering allows the phosphorus in the additive to be distributed on the particle surface of the secondary sintered material to form a phosphorus-rich shell layer; The secondary sintered material is post-processed to obtain the lithium manganese iron phosphate positive electrode material.

[0007] Wherein, the secondary pretreatment includes coarse grinding, fine grinding and drying; after the coarse grinding, the parameter D50 characterizing the slurry particle size is between 0.5 and 2.0 μm, and after the fine grinding, the parameter D50 characterizing the slurry particle size is between 0.2 and 0.5 μm.

[0008] The diameter of the grinding beads used in the coarse grinding is 0.6-1.0 mm, and the diameter of the grinding beads used in the fine grinding is 0.2-0.35 mm.

[0009] The secondary sintering is specifically as follows: heating to a sintering temperature at a rate of 2-5°C / min and sintering for 3-15 hours, wherein the sintering temperature is between 500-850°C.

[0010] Wherein, the sintering temperature is between 600 and 700°C.

[0011] Wherein, the additive is at least one of phosphoric acid, monoammonium phosphate, diammonium phosphate, and lithium dihydrogen phosphate.

[0012] Wherein, the amount of phosphorus in the additive accounts for 0.05-0.5% of the total mass of the secondary sintering material.

[0013] Wherein, the secondary mixed material also includes a carbon-containing compound, and the secondary sintering forms a carbon coating layer on the particle surface of the secondary sintered material, and the carbon-containing compound is at least one of glucose, sucrose, starch, and polyethylene glycol.

[0014] Wherein, the carbon coating layer is located on the outer surface of the phosphorus-rich shell layer.

[0015] In order to solve the above technical problem, another technical solution adopted by the present invention is: to provide a lithium manganese iron phosphate positive electrode material prepared according to the preparation method described in the above technical solution.

[0016] The beneficial effect of the present invention is that, compared with the prior art, in the preparation method of the lithium iron manganese phosphate positive electrode material provided by the present invention, a phosphorus-containing additive is added during the secondary sintering process, so that after the secondary sintering, the phosphorus in the additive is distributed on the particle surface of the secondary sintered material to form a phosphorus-rich shell layer. The phosphorus-rich shell layer can prevent manganese from dissolving during the cycle process, reduce the powder resistivity of the positive electrode material, thereby slowing down the decay rate of the voltage platform during the cycle process, and improving the cycle life of the lithium iron manganese phosphate positive electrode material. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work. Among them: Figure 1 It is a schematic flow chart of an embodiment of a method for preparing a lithium manganese iron phosphate positive electrode material according to the present invention; Figure 2 The performance comparison between the embodiment and the comparative example on the constant current charging ratio is shown; Figure 3 The performance comparison of the embodiment and the comparative example regarding the capacity retention rate is shown in FIG. DETAILED DESCRIPTION

[0018] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0019] See also Figure 1 , Figure 1 The figure is a flow chart of an embodiment of a method for preparing a lithium manganese iron phosphate positive electrode material according to the present invention. The method comprises the following steps: Step S11, mixing the raw materials and the solvent evenly to obtain a primary mixture, wherein the raw materials include a phosphorus-containing compound, a manganese-containing compound, an iron-containing compound, a lithium-containing compound and a carbon-containing compound.

[0020] The raw materials for preparing lithium manganese iron phosphate are the raw materials commonly used in the prior art, phosphorus-containing compounds such as one or more of phosphoric acid, lithium dihydrogen phosphate, and ammonium dihydrogen phosphate, manganese-containing compounds such as one or more of manganese dioxide, manganese tetraoxide, and manganese carbonate, iron-containing compounds such as one or more of ferrous oxalate, ferric phosphate, and ferric oxide, lithium-containing compounds such as one or more of lithium dihydrogen phosphate, lithium carbonate, and lithium phosphate, and carbon-containing compounds such as one or more of glucose, sucrose, starch, and polyethylene glycol, wherein the carbon is mainly used to reduce iron ions in the iron-containing compounds to generate lithium manganese iron phosphate.

[0021] In order to improve the performance of positive electrode materials, oxides, carbonates, phosphates, metal organics, etc. of some elements are usually added to the raw materials to achieve element doping and maintain the material structure, such as Mg, Ti, V, Nb, W, Mo, Er, Co, Ni, Al and other elements.

[0022] The ratio of various raw materials is also the ratio commonly used in the prior art, satisfying the element ratio of lithium manganese iron phosphate. The solvent can be water, and stirring or other methods can be used to promote the mixing of the raw materials and the solvent to obtain a uniformly mixed primary mixture.

[0023] Step S12, performing a pretreatment and a sintering on the primary mixed material to obtain a primary sintered material.

[0024] After the raw materials and the solvent are evenly mixed to obtain a primary mixture, it is first subjected to a pretreatment, specifically coarse grinding, fine grinding and drying in sequence, wherein the coarse grinding and fine grinding can be performed by sand grinding and other methods, and after grinding to a suitable particle size, it is spray dried to remove the solvent, and then subjected to a sintering treatment to obtain a primary sintered material. A chemical reaction occurs during the primary sintering process, and alkaline lithium carbonate usually remains on the surface of the primary sintered material, which has an adverse effect on the performance of the subsequent positive electrode material.

[0025] Step S13, uniformly mixing the primary sintering material, the additive and the solvent to obtain a secondary mixed material, wherein the additive contains phosphorus element.

[0026] After the primary sintering material is obtained, it is evenly mixed with additives and solvents. The solvent can be water or other solvents that can dissolve and disperse the primary sintering material and the additives, wherein the additives contain phosphorus element P, to obtain a secondary mixed material.

[0027] Step S14, performing secondary pretreatment and secondary sintering on the secondary mixed material to obtain a secondary sintered material; the secondary sintering allows the phosphorus in the additive to be distributed on the particle surface of the secondary sintered material to form a phosphorus-rich shell layer.

[0028] After obtaining the secondary mixture, it is first subjected to secondary pretreatment, which specifically includes coarse grinding, fine grinding and drying. The index requirements for coarse grinding and fine grinding are that after coarse grinding, the parameter D50 characterizing the slurry particle size is between 0.5~2.0μm, and after fine grinding, the parameter D50 characterizing the slurry particle size is between 0.2~0.5μm. To achieve this indicator, it is preferred that the diameter of the grinding beads used for coarse grinding is 0.6~1.0mm, and the diameter of the grinding beads used for fine grinding is 0.2~0.35 mm. During the above-mentioned coarse grinding and fine grinding process, the additive can also react with the residual alkali on the surface of the primary sintered material, thereby reducing the alkali content and improving the service life and safety performance of the subsequent positive electrode material.

[0029] After that, the material is subjected to secondary sintering, specifically, the temperature is first raised to the sintering temperature at a rate of 2-5°C / min, for example, 2°C / min, 3°C / min, 4°C / min, 5°C / min, etc., and the sintering temperature is kept at the sintering temperature for 3-15 hours. The sintering temperature is between 500-850°C, for example, 500°C, 550°C, 600°C, 650°C, 700°C, 750°C, 800°C, 850°C, etc., preferably between 600-700°C.

[0030] Among them, the above-mentioned additive is at least one of phosphoric acid, monoammonium phosphate, ammonium dihydrogen phosphate, and lithium dihydrogen phosphate, and the amount of phosphorus element in the additive accounts for 0.05~0.5% of the total mass of the secondary sintering material, for example, 0.05%, 0.1%, 0.15%, 0.2%, 0.25%, 0.3%, 0.35%, 0.4%, 0.45%, 0.05%, etc.

[0031] During the secondary sintering process, the phosphorus element in the additive is enriched on the surface of the material particles, forming a surface phosphorus-rich shell, which has the effect of stabilizing the contact interface between the positive electrode material and the electrolyte.

[0032] Step S15, post-processing the secondary sintered material to obtain lithium manganese iron phosphate positive electrode material.

[0033] After the secondary sintered material is obtained, conventional post-processing operations such as air flow crushing and screening for iron removal are performed on it to obtain the lithium manganese iron phosphate positive electrode material.

[0034] By using the preparation method of lithium iron manganese phosphate positive electrode material provided in this embodiment, the surface of the obtained positive electrode material particles has a phosphorus-rich shell layer, which can prevent manganese from being dissolved during the cycle process, reduce the powder resistivity of the positive electrode material, thereby slowing down the decay rate of the voltage platform during the cycle process, and improving the cycle life of the lithium iron manganese phosphate positive electrode material.

[0035] In some embodiments, the secondary mixture also includes carbon-containing compounds, such as glucose, sucrose, starch, polyethylene glycol, etc. The secondary sintering forms a carbon coating layer on the particle surface of the secondary sintered material. The carbon coating layer is located on the outer surface of the phosphorus-rich shell layer, further reducing the powder resistivity of the material and improving the cycle life of the lithium manganese iron phosphate positive electrode material.

[0036] Based on the same inventive concept, the present invention also provides a lithium manganese iron phosphate positive electrode material, which is prepared by the preparation method in the above embodiment. This embodiment has the same beneficial effects as the above embodiment, which will not be repeated here.

[0037] Based on the same inventive concept, the present invention also provides a lithium-ion battery, which includes the lithium iron manganese phosphate positive electrode material in the above-mentioned embodiment, and of course also includes the negative electrode material, diaphragm, electrolyte, etc. that can be obtained from the scheme disclosed in the prior art. The lithium-ion battery also has the same beneficial effects as the above-mentioned embodiment, which will not be repeated here.

[0038] The performance improvement brought about by the technical solution provided by the present invention is explained below with reference to specific embodiments and comparative examples.

[0039] A positive electrode material is prepared according to the following steps S101-S105, which is recorded as Example 1: Step S101, 17.9 kg of lithium carbonate, 66.9 kg of iron phosphate, 8.53 kg of glucose, 52 kg of manganese tetraoxide, 69.9 kg of lithium dihydrogen phosphate, 1.803 kg of magnesium carbonate, 0.144 kg of titanium dioxide, 0.495 kg of niobium pentoxide, and 220 kg of water are mixed evenly to obtain a primary mixture.

[0040] Step S102, introduce the primary mixed material into a sand mill for coarse grinding (zirconium bead diameter 0.6mm), the primary grinding particle size D50 = 1.3μm; then introduce it into a sand mill for fine grinding (zirconium bead diameter 0.3mm), the grinding particle size D50 = 0.35μm; then spray drying, the spray drying air inlet temperature is 250℃, and the air outlet temperature is 90℃; then sintering is carried out under inert atmosphere protection conditions, rising to 650℃ at a speed of 3℃ / min, keeping warm for 7 hours, and finally cooling to obtain a primary sintered material.

[0041] Step S103 , 100 kg of the primary sintering material, 3.0 kg of glucose, 6.0 kg of polyethylene glycol (molecular weight 6000), 0.8 kg of lithium dihydrogen phosphate (additive) and 110 kg of water are mixed and stirred uniformly to obtain a secondary mixture.

[0042] Step S104, introduce the secondary mixed material into a sand mill for coarse grinding (zirconium bead diameter 0.6mm), coarse grinding to a grinding particle size of D50=0.8μm; then introduce it into a sand mill for fine grinding (zirconium bead diameter 0.3mm), fine grinding to a particle size of D50=0.3μm; then spray drying, the spray drying air inlet temperature is 250℃, and the air outlet temperature is 90℃; then sintering is carried out under inert atmosphere protection conditions, rising to 700℃ at a speed of 3℃ / min, keeping warm for 7 hours, and finally cooling to obtain a secondary sintered material.

[0043] Step S105, air flow pulverizing and sieving the secondary sintered material to remove iron, so as to obtain the lithium manganese iron phosphate positive electrode material of Example 1.

[0044] The difference between Example 2 and Example 1 is that in step S103, the amount of the additive lithium dihydrogen phosphate is 1.2 kg, and the other steps are the same, and finally the lithium iron manganese phosphate positive electrode material of Example 2 is obtained.

[0045] The difference between Example 3 and Example 1 is that in step S103, the amount of the additive lithium dihydrogen phosphate is 1.6 kg, and the other steps are the same, and finally the lithium iron manganese phosphate positive electrode material of Example 3 is obtained.

[0046] The comparative example is different from Example 1 in that in step S103, the above-mentioned additive is not added, and the other steps are the same, and finally the lithium manganese iron phosphate positive electrode material of the comparative example is obtained.

[0047] Please refer to Table 1, which is a comparison of performance data of the embodiments and the comparative examples. The pH value, residual alkali content, powder compaction and resistivity of the positive electrode materials of Embodiment 1, Embodiment 2, Embodiment 3 and the comparative example were respectively measured, and button batteries were respectively made in the same manner. Then, the parameters characterizing the electrical performance (0.1C gram capacity, initial efficiency, 1.0C gram capacity) were respectively measured in the manner disclosed in the prior art.

[0048] It can be seen from Table 1 that with the increase in the amount of additives added, the residual alkali content and pH of the material are significantly reduced, and the gram capacity first increases and then decreases. In addition, the powder resistivity of the material is significantly improved, indicating that the surface of the positive electrode material particles prepared by the present invention has a phosphorus-rich shell layer, thereby reducing the powder resistivity of the positive electrode material.

[0049]

[0050] For further information, see Figure 2 and Figure 3 , Figure 2 and Figure 3They are the performance characterizations of constant current charge ratio and capacity retention rate, from which it can be seen that with the increase in the amount of additives added, the cycle life of the material is greatly improved, and the constant current charge ratio attenuation rate during the cycle process is significantly reduced, indicating that the positive electrode material prepared by the present invention can prevent manganese from being dissolved during the cycle process, thereby slowing down the attenuation rate of the voltage platform during the cycle process and improving the cycle life of the lithium iron manganese phosphate positive electrode material.

[0051] The above description is only an implementation mode of the present invention, and does not limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made by using the contents of the present invention specification and drawings, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.

Claims

1. A method for preparing a lithium manganese iron phosphate positive electrode material, characterized in that: include: The raw materials are mixed evenly with a solvent to obtain a primary mixture, wherein the raw materials include a phosphorus-containing compound, a manganese-containing compound, an iron-containing compound, a lithium-containing compound and a carbon-containing compound; The primary mixed material is subjected to a pre-treatment and a sintering to obtain a primary sintered material; The primary sintering material, additive and solvent are uniformly mixed to obtain a secondary mixed material, wherein the additive contains phosphorus element; The secondary mixed material is subjected to secondary pretreatment and secondary sintering to obtain a secondary sintered material; the secondary sintering allows the phosphorus in the additive to be distributed on the particle surface of the secondary sintered material to form a phosphorus-rich shell layer; The secondary sintered material is post-processed to obtain the lithium manganese iron phosphate positive electrode material.

2. The preparation method according to claim 1, characterized in that: The secondary pretreatment includes coarse grinding, fine grinding and drying; after the coarse grinding, the parameter D50 characterizing the slurry particle size is between 0.5 and 2.0 μm, and after the fine grinding, the parameter D50 characterizing the slurry particle size is between 0.2 and 0.5 μm.

3. The preparation method according to claim 2, characterized in that: The diameter of the grinding beads used in the coarse grinding is 0.6-1.0 mm, and the diameter of the grinding beads used in the fine grinding is 0.2-0.35 mm.

4. The preparation method according to claim 1, characterized in that: The secondary sintering is specifically as follows: The temperature is raised to the sintering temperature at a rate of 2-5°C / min, and sintered for 3-15 hours, wherein the sintering temperature is between 500-850°C.

5. The preparation method according to claim 4, characterized in that: The sintering temperature is between 600 and 700°C.

6. The preparation method according to claim 1, characterized in that: The additive is at least one of phosphoric acid, monoammonium phosphate, diammonium phosphate, and lithium dihydrogen phosphate.

7. The preparation method according to claim 6, characterized in that: The amount of phosphorus in the additive accounts for 0.05-0.5% of the total mass of the secondary sintering material.

8. The preparation method according to claim 1, characterized in that: The secondary mixed material also includes a carbon-containing compound. The secondary sintering forms a carbon coating layer on the particle surface of the secondary sintered material. The carbon-containing compound is at least one of glucose, sucrose, starch, and polyethylene glycol.

9. The preparation method according to claim 8, characterized in that: The carbon coating layer is located on the outer surface of the phosphorus-rich shell layer.

10. A lithium manganese iron phosphate positive electrode material prepared according to the preparation method according to any one of claims 1 to 9.

Citation Information

Cited By

  • Lithium manganese iron phosphate positive electrode material and preparation method therefor

    EP4574754A1